Direction of Government Policy regarding the Position of Madrasahs in the National Education System - Aep Saepul Anwar; Tobroni Tobroni; Faridi Faridi; Dede Ridho Firdaus (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2026)
This study examines the direction of government policies in positioning madrasahs within Indonesia’s national education system, with particular attention to institutional equivalence, curriculum reform, religious moderation, and policy implementation. Employing a qualitative document analysis approach, the study analyzes Law Number 20 of 2003 on the National Education System, Permendikdasmen Number 13 of 2025, and the Madrasah Development Roadmap 2025–2029. Data were analyzed through directed content analysis using themes of legal recognition, resource equity, teacher professional development, curriculum integration, religious moderation, and inter-institutional coordination. The findings indicate that government policies have progressively strengthened the formal status of madrasahs as educational institutions equivalent to public schools. Curriculum reform represents the most significant policy advancement through the integration of Islamic education, critical thinking, creativity, collaboration, digital literacy, and religious moderation. However, the implementation of these policies remains constrained by governance dualism between the Ministry of Religious Affairs and the Ministry of Education, unequal budget allocation, regional infrastructure disparities, differences in teacher qualifications, and the absence of binding inter-ministerial coordination mechanisms. The analyzed policies provide comprehensive strategic direction but remain predominantly aspirational because they lack clear implementation timelines, performance indicators, funding arrangements, and accountability structures. This study concludes that strengthening madrasahs requires enforceable cross-ministerial governance, equitable resource distribution, standardized teacher development, and continuous monitoring of policy outcomes. The study is limited by its reliance on policy documents; therefore, future research should empirically investigate policy implementation in urban and rural madrasahs through mixed-method and comparative approaches.